DIABETES MELLITUS FROM THE POINT OF VIEW OF ADOLESCENTS - Larissa Evangelista Ferreira; Elisangela Argenta Zanatta; Maria Luiza Bevilaqua Brumm; Simone Cristine dos Santos Nothaft; Maria da Graça Motta (Universidade Federal do Paraná, 2013)
This qualitative research, undertaken in 2011 with eight adolescents with Type 1 diabetes mellitus aimed to investigate limitations which these experience, faced with the illness in the family, social and eating ambits. The Dynamic of Creativity and Sensitivity called for by the Creative and Sensitive Method was used for data collection. The interpretation of the information followed thematic content analysis, giving rise to two categories: Diabetes in the life of the adolescent and Limitations imposed by the illness. The results indicate a range of feelings, such as hope, happiness and sadness, and difficulties, such as the requests made by health professionals and parents, strict schedules for medication, and living with hypoglycemic crises. The limitations relate to the difficulties in being accepted and co-existing with friends, and restrictions on diet. The research raised important elements which support those observed in other studies, providing support for the elaboration of nursing care for the adolescent with diabetes.